[PP.14.12] PREVALENCE OF ATRIAL FIBRILLATION IN HYPERTENSIVE SUBJECTS: WHAT IS MORE IMPORTANT –BLOOD PRESSURE VALUES OR DURATION OF HYPERTENSION?. (September 2016) - Yotov, Y.; Torbova, S.; Ramshev, K.; Tisheva, S.
Abstract : Objective: To evaluate the predictive factors for occurrence of atrial fibrillation in hypertensive patients. Design and method: Overall, 3684 volunteers with AH from 11 cities of Bulgaria participated in a cross-sectional study on the World Hypertension Day in 2014 and 2015. Same structured questionnaire was applied in the two surveys with questions about the registered episodes of AF, symptoms, treatment, demographic characteristics, diabetes mellitus, and home blood pressure measurement (BP). The BP, heart rate, weight and waist circumference were measured, BMI was calculated. Results: The mean age of the participants was 59.81 ± 16.44 years, 55% were female. The median duration of AH was 9 years. AF was present in 386 (11%) of them and in 282 (73%) of those with the arrhythmia it was treated, with no difference by year of examination or gender. New AF was diagnosed in 4% in this hypertensive population. The mean blood pressure was 141.86 ± 22.14/85.46 ± 11.97 mmHg in males and 133.75 ± 20.27/79.67 ± 10.99 mmHg in females (p < 0.001). The prevalence of AF was not significantly correlated with the BP values or with the quartiles of the BP distribution. However, the mean duration of AH was significantly longer in the patients with the arrhythmia compared to those in sinus rhythm – 14.1 vs 10 years for the known AF (p < 0.0001) and 14.75 vs 10.65 years for new AF (p < 0.0001). The hypertensive patients with AF (new or known) had almost twice more frequently duration of AH longer than the median (>9 years) than those without the arrhythmia – 23.4% vs 12.2% (p < 0.0001). In multiple logistic regression analysis, the hypertensive patients with onset of their AH more than 9 years had twice higher risk of developing AF (RR = 2.03, 95%CI 1.52–2.69, p < 0.0001), after adjustment for age, sex, measures of obesity, presence of diabetes, and BP. Conclusions: The prevalence of AF in an urban hypertensive population was approximately 1 in 8. Neither the present values of BP nor the severity of AH at the moment had effect on the occurrence of AF. The most powerful predictor of AF was the duration of AH more than the median.